Risk factors for self‐reported insufficient milk during the first 6 months of life: A systematic review - Sofia Segura‐Pérez; Linda Richter; Elizabeth C. Rhodes; Amber Hromi‐Fiedler; Mireya Vilar‐Compte; Misikir Adnew; Kate Nyhan; Rafael Pérez‐Escamilla (Wiley, 2022)
Abstract The objective of this systematic review was to identify multifactorial risk factors for self‐reported insufficient milk (SRIM) and delayed onset of lactation (DOL). The review protocol was registered a priori in PROSPERO (ID# CDR42021240413). Of the 120 studies included (98 on SRIM, 18 on DOL, and 4 both), 37 (31%) studies were conducted in North America, followed by 26 (21.6%) in Europe, 25 (21%) in East Asia, and Pacific, 15 (12.5%) in Latin America and the Caribbean, 7 (6%) in the Middle East and North Africa, 5 (4%) in South Asia, 3 (2.5%) in Sub‐Saharan Africa, and 2 (1.7%) included multiple countries. A total of 79 studies were from high‐income countries, 30 from upper‐middle‐income, 10 from low‐middle‐income countries, and one study was conducted in a high‐income and an upper‐middle‐income country. Findings indicated that DOL increased the risk of SRIM. Protective factors identified for DOL and SRIM were hospital practices, such as timely breastfeeding (BF) initiation, avoiding in‐hospital commercial milk formula supplementation, and BF counselling/support. By contrast, maternal overweight/obesity, caesarean section, and poor maternal physical and mental health were risk factors for DOL and SRIM. SRIM was associated with primiparity, the mother's interpretation of the baby's fussiness or crying, and low maternal BF self‐efficacy. Biomedical factors including epidural anaesthesia and prolonged stage II labour were associated with DOL. Thus, to protect against SRIM and DOL it is key to prevent unnecessary caesarean sections, implement the Baby‐Friendly Ten Steps at maternity facilities, and provide BF counselling that includes baby behaviours.